Marketing strategy in corporate context - Foxall, Gordon R.; Driver, John C. (Cranfield School of Management, 1986)
There is a growing body of thought - reflected in a burgeoning literature - which champions the benefits of 'strategic marketing' as a means of corporate salavation. This article seks to put marketing into its correct corporate context - not as the ultimate locus of strategic planning and action, but as a managerical function concerned with the implementation of a philosophy of creating profitable customer satisfaction. The article argues that currently-fashionable excesses among those who apparently seek the aggrandisement of the marketing function make necessary this re-affirmation of the role of marketing management.